KEBIJAKAN RETRIBUSI PERIZINANUSAHA PARIWISATA DI KOTA PONTIANAK - Firdaus E.01107028 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
The problem in this study is the low awareness of compulsory levy to pay the levy licensing tourism business license , the imposition of sanctions and measures against compulsory levy that does not meet its obligations , less strict so that the unwillingness to pay more protracted , low motivation apparatus of Culture and Tourism in Pontianak carry out tasks such as lack of education about tourism business license permits to businesses , and the existence of tourism businesses have ups and downs that resulted in some people not to extend its tourism business license . This study aims to describe the process of policy implementation Permits Tourism in the Department of Culture and Tourism of Pontianak . This type of research in this study is qualitative descriptive research which examined the problem solving done by giving an overview of the situation by using the data and the facts found by the time the study was conducted . The research found that the process of communication that exists within the discretion of the tourism business license withdrawal charges running less effective . The results showed that the dissemination of tourism business license regulations made ??by the Department of Culture and Tourism of Pontianak to businesses only once a year . This led to some people who do not know the procedure , the purpose and benefits of taking care of the tourism business license . Responding to the suggestion that there is a phenomenon that should be recommended Pontianak City Government should make it easier for service in the field of tourism such as tourism licensing Hotels , Restaurants , coffee shops , fitness centers through the establishment of a new law , or the Mayor 's decision . Besides Pontianak City Government should further improve infrastructure , because it is a major contributory factor to facilitate services to the public .Keywords : Policy , Levy , Tourism Enterprises.